Funding Agricultural Innovation for the Global South: Does it Promote Sustainable Agricultural Intensification? - Dalberg Asia (Commission on Sustainable Agriculture Intensification, 2021)
This study, carried out in 2020-21 by Dalberg Advisors Asia (relying on secondary and primary funding data, modeling, and expert discussions), answers some of these key questions. The study covers four key categories of funders – (i) Global South Governments (domestic funding), (ii) Development Partners, (iii) Private Companies, and (iv) Private Equity/Venture Capital (PE/VC) funds. It studies their funding across the last decade (2010-2019) for the Global South and seeks to achieve a baseline understanding of these funding patterns. While private funding by farmers and other agricultural producers can be significant, they are excluded from this report’s analysis due to the study focus and lack of available data.